Effects of automatisation and digitalisation on manufacturing companies' production efficiency and innovation performance - Henning Kroll; Djerdj Horvat; Angela Jäger (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2018)
[Introduction] In recent years, the debate on the digitalisation of industry has gained momentum not only in the political, but also in the academic sphere. As part of a broader debate on the digitisation of life, it has touched upon many relevant dynamics of industrial transformation that will, without doubt, substantially affect the way in which production as such takes place as well as the role it plays in and for diverse value chains and innovation networks. However, as much as the digitalisation debate addresses pertinent questions for future industrial innovation and production, much of it continues to suffer from a lack of clarity regarding both the very substance of the discussion and the factual consequences that it already develops in the industrial sphere. The first and arguably most pressing issue is that while the term "digitisation" succinctly captures a generic societal trend, it conveys comparatively little about the actual (catalogue of) technologies that we mean by it. A debate that moves from a general observation of "digitisation" to a more focused analysis of "industrial digitalisation" can only then yield relevant results if it is specific about the concrete technologies involved and the concrete effects in industrial innovation and production that can be expected. In the majority of cases, specific papers like this one, will only be able to address spread and effect of a certain number of digital technologies. So far, many parts of the discussion fail to deliver on these needs for differentiation not only with regard to the concrete technologies additionally deployed but also with regard to the changes in firm performance that they are supposed to trigger. While mutually related, industrial innovation and industrial production remain distinct areas on and in which the impact of "industrial digitalisation" needs to be studied separately as the set of concrete digital technologies which matter for them differs substantially. Consequently, this paper suggests that it appears reasonable to distinguish between the diverse cause-effect relationships that occur in the course of the spread of digitalisation. These need to be clearly formulated with respect to their technological foundation as well as the area of industrial activity in which change is triggered. Hence, it proposes that a structured understanding of the broad dynamic of digitalisation that we are witnessing needs to be gradually built by hypothesising, confirming and disconfirming specific relationships. Furthermore, it appears likely that "digitalisation" of industry will take effect gradually, in a step-by-step manner, as did all past breakthrough innovations from the introduction of the steam engine and, later, electricity into the production system to the various changes in the prevalent means of transportation that the past two centuries have witnessed. Typically, the invention of breakthrough technologies first spurred a development of more, related technologies before those technologies became fully implemented as prevalent means in the production system.
urn:nbn:de:0011-n-4873361
Keywords: 330